Assessing Competencies and Challenges Among Non-BSE Social Science Major Enrolled in MAED Social Science Program: Basis for Program Enhancement - Mamauag, Eden (Studies in Technology and Education, 2026)
This study assessed the competencies and challenges among non-Bachelor of Secondary Education Social Science majors enrolled in the Master of Arts in Education Social Science Program at Isabela State University, Echague, Isabela. A total of 31 respondents participated in the study. The research employed a descriptive-correlational design and utilized survey questionnaires to gather data on the respondents' demographic profile, pedagogical competency levels, and perceived teaching challenges across four dimensions. The results show that majority of respondents were in the 31–40 years old age group, predominantly female, and had 6–10 years of teaching experience. No respondent reported more than 10 years of teaching experience. Level of Pedagogical Competency. Non-BSE Social Science majors perceive themselves as generally competent in their pedagogical practices. The highest-rated competencies were demonstrating professionalism and ethical teaching behavior and adapting lessons to diverse learners, both rated "Excellent." The lowest-rated competencies were reflecting on teaching practices and planning and delivering lessons effectively. Common Challenges. Academic Preparedness yielded the highest challenge mean followed by Teaching Skills Development, Resource Accessibility, and Program Alignment Issues. Overall, respondents did not strongly identify these as major challenges. Age showed significant differences in two competency indicators such as technology use and classroom discipline management, with older respondents rating themselves higher. Years of teaching experience showed highly significant differences in 14 out of 15 competency indicators, with respondents having 6–10 years of experience consistently rating themselves at "Excellent" levels. A predominantly significant and negative relationship was found between pedagogical competency levels and perceived teaching challenges. Based on the result of the study, it recommends that the MAEd Social Science Program Administrators should incorporate structured academic bridging sessions designed specifically for non-BSE Social Science majors, particularly in the areas of theoretical integration and academic reading of Social Science topics. Faculty members should deliberately incorporate reflective teaching activities such as teaching journals, peer observation, and portfolio assessments into course requirements.